2004
DOI: 10.1016/j.jebo.2002.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocity in a two-part dictator game

Abstract: We conduct a dictator game experiment in which recipients in an initial game become dictators in a second game. When the subjects paired remain the same, the amount sent back is strongly correlated with the amount received despite the fact that the interaction is anonymous and is known to be one-time and zero-sum in nature. When the initial recipient is instead paired with a third subject, a less significant and lower-valued correlation between amounts received and sent is exhibited. Intelligence and personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(98 citation statements)
references
References 37 publications
4
91
0
3
Order By: Relevance
“…Ben-Ner, Putterman, Kong, and Magan (2004) found that a history of religious training leads to greater offers in a two-part Dictator game, but is not associated with reciprocation by the other player. Tan (2006), using Dictator and Ultimatum games among German participants, found that his overall measure of religiosity that combined various dimensions (belief, experience, and ritual) was not predictive of gameplay.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Ben-Ner, Putterman, Kong, and Magan (2004) found that a history of religious training leads to greater offers in a two-part Dictator game, but is not associated with reciprocation by the other player. Tan (2006), using Dictator and Ultimatum games among German participants, found that his overall measure of religiosity that combined various dimensions (belief, experience, and ritual) was not predictive of gameplay.…”
mentioning
confidence: 89%
“…Participants played the Dictator game following the elaborate double-blind procedures pioneered by Hoffman, McCabe, Shachat, and Smith (1994) and modified by Ben-Ner et al (2004). This procedure gives individuals complete privacy when making their decision, and gives them almost complete anonymity from the experimenter.…”
Section: Designmentioning
confidence: 99%
“…Following Chen et al (1998), Long (1983, and Danziger et al (2008), we therefore separate the creativity items to form the creativity factor C (two items, α = 0.76), while the other items form the (entrepreneurial) business talent factor BT (ten items, α = 0.79). 12 Similar to Ben-Ner et al (2004), who investigate the extent to which personality can affect behavior in dictator games, we also include the 'Big Five' personality traits, which describe five broad psychological factors or dimensions of personality: extraversion, agreeableness, conscientiousness, neuroticism, and openness. Although they have been found to be related to entrepreneurship (Zhao et al, 2010;Gruber, forthcoming), we acknowledge that there exists an inconclusive discussion whether such general traits have potential in explaining entrepreneurial behavior (see Rauch and Frese, 2007).…”
Section: Page 11 Of 34mentioning
confidence: 99%
“…From the answers they gave, we can be confident they were really unaware of the experimental hypotheses. Finally, as explained above (see Section 5.2.1), we collected and included in our regressions a large number of controls that have been proved to be associated with nice and reciprocating behaviour (Ben-Ner et al (2004); Giannetti and Orsini (2014)). …”
Section: Discussionmentioning
confidence: 99%